Exploring the use of e-portfolios in higher education coaching programs - Dray, K.; Howells, K. (International Sport Coaching Journal, 2019)
The contribution of higher education to the development of the coaching workforce worldwide has been most recently emphasised by the development of the ICCE`s Coaching Degree Standards (2016). These standards recognise the increasing value of learning technologies, suggesting that the use of technology in such coaching programs should aim to a) "enhance the learning experience of the student-coach" and b) "gain relevant theoretical and practical knowledge to make the most of technology whilst coaching" (p. 23). This article presents one coach developer`s experience of using e-portfolios with undergraduate students on a BSc. Sport Coaching Science undergraduate program that represents an effort to address both of these aims simultaneously. Drawing from a broader field of education research and through the provision of examples, it is suggested that e-portfolios might afford the coach learner a number of benefits including their accessibility, the role they play in developing meta-cognition, and their ability to provide a space that can bring together the different communities that influence the learner. Lastly, the benefits and challenges are presented through the eyes of the academic tutor and the relevance for coach education contexts outside of HE are discussed.